Seven new species of Cichlidogyrus Paperna, 1960 (Monogenea: Dactylogyridae) parasitizing the gills of Congolese cichlids from northern Lake Tanganyika - Rahmouni, Chahrazed; Vanhove, Maarten P M; Šimková, Andrea (PeerJ, 2018)
Seven new species of Cichlidogyrus Paperna, 1960 (Monogenea: Dactylogyridae) isolated from the gills of six cichlid host species belonging to four tribes and sampled from the Congolese coastline of Lake Tanganyika (LT) are described: Cichlidogyrus adkoningsi sp. nov. from Cyphotilapia frontosa (tribe Cyphotilapiini); C. koblmuelleri sp. nov. from Cardiopharynx schoutedeni (Ectodini); C. habluetzeli sp. nov. from C. schoutedeni and C. frontosa; C. antoineparisellei sp. nov. from Interochromis loocki (Tropheini); C. masilyai sp. nov. from Petrochromis orthognathus (Tropheini); C. salzburgeri sp. nov. from P. trewavasae, and C. sergemorandi sp. nov. from Tylochromis polylepis (Tylochromini). This study represents the first parasitological examination of cyphotilapiine cichlid hosts. Representatives of the Tanganyikan ectodine, tropheine, and tylochromine cichlids previously sampled from various localities in the lake yielded nine, twelve, and two described species of Cichlidogyrus, respectively. The study further includes a morphological characterization of the male copulatory organ of six undescribed species of Cichlidogyrus found on the gills of the tropheines I. loocki and P. orthognathus, and on those of Callochromis melanostigma and Xenotilapia flavipinnis (both Ectodini). Geographical variation in the monogenean fauna of I. loocki was observed. The most closely related cichlid species investigated in this study harboured Cichlidogyrus spp. exhibiting some similarities in their sclerotized structures. Thus, our paper provides additional evidence of the high species richness of Cichlidogyrus and the link with their hosts's phylogenetic affinities in LT.
Keywords: Congo; Cardiopharynx; C. masilyai sp. nov.; Petrochromis; Interochromis; C. antoineparisellei sp. nov.; C. sergemorandi sp. nov.; C. habluetzeli sp. nov.; Cichlidae; Tylochromis; C. koblmuelleri sp. nov.; Platyhelminthes; Cyphotilapia; C. adkoningsi sp. nov.; Xenotilapia; Callochromis; C. salzburgeri sp. nov.